Poetics at the Religious Margin: Bernard Barton and Quaker Romanticism. (8th January 2019) - Stokes, Christopher
Abstract: This article examines the emergence of a Quaker literary sub-culture in the nineteenth century through an analysis of the work of Bernard Barton, the first Quaker poet to gain cultural prominence. Although the Society of Friends was perceived as a quintessentially unpoetic sect with little or no literary history, Barton developed a poetics that resonated with contemporary readers despite, and in some ways because of, its Quaker inflections. After tracing the lineaments of his authorial persona, in both reviews and his own self-fashioning, I examine the way in which Barton re-works Romantic-era literary styles and modes: first through a consideration of three specific intertextual dialogues, and then through a more general reading of his nature and landscape verse. What emerges is a body of poetry that is marked by Quakerism in thematic aspects, such as radical pacifism and the quietist spirituality of silence, but also through consistent and coherent tendencies of style. In the context of Quaker plainness and reserve, Barton adopts and adapts a range of aesthetic traits, ranging from the Spenserian stanza to forms of picturesque, to construct a poetics of simplicity underpinned by his favoured rhetorical stance of litotes . In doing so, he makes the paradoxical proposition of a Quaker poet imaginable for a nineteenth-century readership.